2017
DOI: 10.1016/j.applanim.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees with positive welfare are happier, extraverted, and emotionally stable

Abstract: Facilities housing captive animals are full of staff who, every day, interact with the animals under their care. The expertise and familiarity of staff can be used to monitor animal welfare by means of questionnaires. It was the goal of our study to examine the association between chimpanzee (Pan troglodytes) welfare, happiness, and personality. To these ends we collected two waves of welfare and subjective well-being ratings of 18 chimpanzees housed at the Edinburgh Zoo and one set of ratings of 13 chimpanzee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 54 publications
(73 reference statements)
5
37
0
Order By: Relevance
“…As in our study of a subsample of these subjects (34), we found a pattern of personality-subjective well-being correlations that were consistent with those found in studies of humans (36,37) and nonhuman primates (29,(38)(39)(40)(41)(42). Similar associations have also been reported for felids (84,85).…”
Section: Discussionsupporting
confidence: 91%
“…As in our study of a subsample of these subjects (34), we found a pattern of personality-subjective well-being correlations that were consistent with those found in studies of humans (36,37) and nonhuman primates (29,(38)(39)(40)(41)(42). Similar associations have also been reported for felids (84,85).…”
Section: Discussionsupporting
confidence: 91%
“…Each primate is usually rated on a scale of 1-7 (alternatively 1-5) in a number of aspects (e.g., fearfulness, sociability, playfulness) by people who are familiar with the focal individual -typically caregivers or researchers working with the individual for a long time. This method is most common in apes (Weiss et al 2007, 2012, moRton et al 2013, RoBinson et al 2017, hence the name of the most popular questionnaire -Hominiod Personality Questionnaire. In this measure, caretakers are asked to score whether the animal is above, below, or average (on a 1-7 scale) for 51 selected traits, e.g., dominant or curious (Weiss et al 2009).…”
Section: A P P R O a C H E S T O P E R S O N A L I T Y R E S E A R C mentioning
confidence: 99%
“…Keeper‐centric data collection frameworks have taken a variety of forms, often tailored to the resources and the most pressing questions related to species management, and have been applied to a wide range of species including black rhinoceros ( Diceros bicornis ; Carlstead et al, ); cheetah ( Acinonyx jubatus ; Wielebnowski, ); gorilla ( Gorilla gorilla gorilla ; Less, Kuhar, Dennis, & Lukas, ); and Asian elephant ( Elephas maximus ; Duer, Tomasi, & Abramson, ). Robinson et al (, ) demonstrated that keeper questionnaires can be a useful tool in collecting data on animal welfare and personality. These examples provide a strong theoretical framework for the value of keeper feedback in assessing animal behavior (King & Landau, ; Whitham & Wielebnowski, ).…”
Section: Introductionmentioning
confidence: 99%